SLIP OF THE TONGUE IN BBC NEWS ANCHORS’ VIDEOS IN TEXTUAL PRONUNCIATION CONTEXT - Paradewari, Dirtya Sunyi; Bram, Barli (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
One of the speech error phenomena is a slip of the tongue, which frequently occurs in pronunciation. Accordingly, the paper intended to address two questions. First, what are the types of the slip of the tongue found in BBC news anchors’ utterances? Second, what are the frequency effects that influence the slips of the tongue in the videos? Data were collected from YouTube videos of BBC news anchors in textual pronunciation, namely pronunciation in context. The analysis was conducted based on the types of slips of the tongue and frequency effects. Results showed that the three types of slips of the tongue occurring in the videos were anticipation, perseverations, and exchange. The four frequency effects identified in the videos were the lexical expectation effect, the speaking rate effect, the type effect, and the location similarity effect.